2009
DOI: 10.1002/pmic.200800802
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for surveying the proteome using affinity proteomics and mass spectrometry

Abstract: Radiation-induced gliomas represent a relatively rare but well-characterized entity in the neuro-oncologic literature. Extensive retrospective cohort data in pediatric populations after therapeutic intracranial radiation show a clearly increased risk in glioma incidence that is both patient age- and radiation dose/volume-dependent. Data in adults are more limited but show heightened risk in certain groups exposed to radiation. In both populations, there is no evidence linking increased risk associated with rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 71 publications
1
43
0
2
Order By: Relevance
“…However, in our case, this was a deliberate motif strategy based on the fact that the GPS set-up was designed to target tryptic peptides. [21][22][23] It could be anticipated that the same phenomena would be observed using proteases favoring different cutting sites, although this remains to be experimentally verified. The impact of adding extra residues to the C-terminal end of the peptides also remains to be directly evaluated.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…However, in our case, this was a deliberate motif strategy based on the fact that the GPS set-up was designed to target tryptic peptides. [21][22][23] It could be anticipated that the same phenomena would be observed using proteases favoring different cutting sites, although this remains to be experimentally verified. The impact of adding extra residues to the C-terminal end of the peptides also remains to be directly evaluated.…”
Section: Discussionmentioning
confidence: 90%
“…The set of tryptic peptides bound by each individual CIMS antibody was thus detected and identified using tandem-mass spectrometry. The results showed that peptides of a median length of 10 amino acids (range [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and with a median pI of 6.5 (range 3.8-12) were captured in a clone-dependent manner (Table I). Noteworthy, as illustrated for the CIMS-17 sister pair, the affinity (K D ) for an experimentally verified captured yeast peptide was found to be in the same range as that observed for the original selection peptide (Table I).…”
Section: Degenerate Peptide-binding Specificitymentioning
confidence: 93%
See 2 more Smart Citations
“…However, LC-MS cannot match proteins identified by software with their Mr and pI, and another major limitation is that this technique is not suitable for quantitative analysis. 59,65 To overcome the shortcomings of 2DE and LC as individual techniques, this study 21,30,32 combined 2DE and LC to explore protein changes in cells and tissues. In mouse testis, we used 2DE to construct an overall proteome profile and comparative proteome profiles of different stages of spermatogenesis, which revealed that many proteins appeared as two or more spots.…”
Section: Hormone-induced Suppression Model Of Spermatogenesismentioning
confidence: 99%